1986
DOI: 10.1073/pnas.83.3.674
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of aortic smooth muscle cell mitogenesis by serotonin.

Abstract: Bovine aortic smooth muscle cells in vitro responded to 1 nM to 10 ,M serotonin with increased incorporation of [3H]thymidine into DNA. The mitogenic effect of serotonin was half-maximal at 80 nM and maximal above 1 ,uM. At a concentration of 1 ,uM, serotonin stimulated smooth muscle cell mitogenesis to the same extent as human plateletderived growth factor (PDGF) at 12 ng/ml, Tryptamine was =1/10th as potent as serotonin as a mitogen for smooth muscle cells. Other indoles that are structurally related to sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(133 citation statements)
references
References 19 publications
6
127
0
Order By: Relevance
“…Such cross talk between ECs and SMCs mediated by 5-HT appears unique to the pulmonary circulation, because 5-HT does not seem to act as a potent mitogenic factor on SMCs in systemic vessels. 5,28 Third, dysregulation of lung 5-HT synthesis by P-ECs appears to make a major contribution to smooth muscle hyperplasia in iPH. We found that TPH expression and 5-HT synthesis were increased in P-ECs from patients with iPH compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Such cross talk between ECs and SMCs mediated by 5-HT appears unique to the pulmonary circulation, because 5-HT does not seem to act as a potent mitogenic factor on SMCs in systemic vessels. 5,28 Third, dysregulation of lung 5-HT synthesis by P-ECs appears to make a major contribution to smooth muscle hyperplasia in iPH. We found that TPH expression and 5-HT synthesis were increased in P-ECs from patients with iPH compared with control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin, a neurotransmitter and a substance released from degranulating platelets, was likewise observed to stimulate smooth muscle cell replication. 289 Angiotensin II, another potent vasoconstrictor, appears to be an exception from this rule. It binds to receptors on cultured vascular smooth muscle cells, 290291 and stimulates several steps in the signal transduction machinery for growth factors and hormones.…”
Section: Role Of Vasoactive Hormonesmentioning
confidence: 99%
“…33 Five hours later DNA was extracted 34 , and DNA [ 3 H] content was measured using a ␤-counter. Experiments were conducted in phenol red-free medium to avoid estrogen-like and antioxidant effects.…”
Section: Cell Proliferationmentioning
confidence: 99%